2005
DOI: 10.1042/bj20041257
|View full text |Cite
|
Sign up to set email alerts
|

The first cysteine-rich domain of the receptor GFRα1 stabilizes the binding of GDNF

Abstract: The GDNF (glial cell line-derived neurotrophic factor)-binding receptor GFRα1 (GDNF family receptor α1) is attached to the membrane by a GPI (glycosylphosphatidylinositol) anchor and consists of three cysteine-rich domains. The region corresponding to the second and third domains has been shown previously to participate in ligand binding, and to interact with the transmembrane tyrosine kinase receptor RET. No function has so far been found for the N-terminal, first domain (D1). Here we show that the GPI-anchor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 32 publications
(64 reference statements)
0
12
0
Order By: Relevance
“…To obtain a secretable form of Gas1, we generated truncated forms of Gas1, lacking the GPI-link consensus sequence, so these forms of Gas1 will be secreted from the cells. 14,38,39 The autocrine and paracrine effects of Gas1 will significantly increase its therapeutic capacity, by allowing the diffusion and distribution of the therapeutic molecule away from producer cells. To reach this objective we generated lentivirus expressing a truncated form of Gas1 (Arg 315), and determined that infected cells release a soluble form of Gas1 that can induce cell arrest and apoptosis when transferred to independent cultures of C6 cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To obtain a secretable form of Gas1, we generated truncated forms of Gas1, lacking the GPI-link consensus sequence, so these forms of Gas1 will be secreted from the cells. 14,38,39 The autocrine and paracrine effects of Gas1 will significantly increase its therapeutic capacity, by allowing the diffusion and distribution of the therapeutic molecule away from producer cells. To reach this objective we generated lentivirus expressing a truncated form of Gas1 (Arg 315), and determined that infected cells release a soluble form of Gas1 that can induce cell arrest and apoptosis when transferred to independent cultures of C6 cells.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10] We also showed that Gas1 exhibits significant structural homology with Glial-cell-line-derived neurotrophic factor (GDNF) receptors (GFRas) and demonstrated that Gas1 inhibits GDNF-mediated intracellular signaling cascades, therefore, shutting down cellular survival pathways. [10][11][12] As the effect of Gas1 interfering with the function of the GFRa-GDNF-Ret complex is due to its structural similarity to GFRas, and it is known that GFRa1 can be released from cells and in this soluble form binds and interacts with GDNF, at the level of the first cysteine-rich domain of the GFRa1, 13,14 we hypothesized that a secreted, soluble Gas1 protein, could exert its inhibitory effect both in the cells that produce soluble Gas1 and in neighbor cells, thus extending its therapeutic capacity to treat tumors. Moreover, there is a report indicating that soluble Gas1, produced in COS7 cells, is functional.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rat GFRa1 construct used in this work (accession number AJ002072) was tagged with the FLAG epitope and has previously been characterized (Virtanen et al, 2005). The human RET constructs (long isoform, accession number NM_000323) were from Marc Billaud (Pelet et al, 1998), and were subcloned into pCR3.1.…”
mentioning
confidence: 99%
“…All point mutations were introduced by inverse PCR mutagenesis, and all DNA constructs were sequenced throughout. PC6-3 cells (a subclone of PC12 cells) do not express GFRa1 and have very low levels of endogenous RET (Virtanen et al, 2005). All transfections were carried out using Lipofectamine TM 2000 (Invitrogen, Carlabad, CA, USA) unless otherwise indicated.…”
mentioning
confidence: 99%